2011
DOI: 10.1007/s10508-011-9790-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Similarities in Married Couples: Patterns Across and Within Cultures

Abstract: In this study, we examined the patterns of sex differences in men and women married to each other in five cultures (China, Russia, Turkey, UK, and the U.S.) to look for universal patterns in behavioral dimorphisms and for cultural variability in those patterns. Over 400 couples in each cultural group completed the 235-item Marriage and Relationship Questionnaire on various aspects of marriage, appropriately translated for each culture. Sex differences were anticipated in responses related to female choosiness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Perilloux and Buss 2008). Additionally, this finding provides converging evidence for previous research on women's greater propensity to be choosier in the quality of relationship deemed necessary to continue the relationship even after initial mate selection (Umberson et al 2006;Weisfeld et al 2011) as well as consequent relationship dissolution (Hill et al 1976;Kalmijn and Poortman 2006;Morris et al 2015).…”
Section: Breakup Initiation and Post-breakup Emotionssupporting
confidence: 69%
“…Perilloux and Buss 2008). Additionally, this finding provides converging evidence for previous research on women's greater propensity to be choosier in the quality of relationship deemed necessary to continue the relationship even after initial mate selection (Umberson et al 2006;Weisfeld et al 2011) as well as consequent relationship dissolution (Hill et al 1976;Kalmijn and Poortman 2006;Morris et al 2015).…”
Section: Breakup Initiation and Post-breakup Emotionssupporting
confidence: 69%
“…;” “Do you enjoy your husband's/wife's company?” ) on a five-point scale (1 = no ; 2 = rather no ; 3 = neither yes nor no ; 4 = rather yes ; 5 = yes ). This subscale has been tested for cross-cultural use and showed good psychometric characteristics in many cross-cultural studies (Lucas et al, 2004 , 2008 ; Weisfeld et al, 2011 ). In the current study, internal consistency (Cronbach alpha) was 0.91 across all samples and both genders.…”
Section: Methodsmentioning
confidence: 99%
“…It seems that women highly value work–life balance; thus, worksite or institutional support is a key factor in promoting childbirth, especially in promoting subsequent childbirth, among employed women. Previous cross-cultural research found that women prefer to housework more than men [ 26 ]; thus, housework may not be a harsh burden for all women. Actually, women provide more childcare than men in all cultures [ 27 ], including Korea.…”
Section: Discussionmentioning
confidence: 99%